2021
DOI: 10.3390/ijms22063184
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from COVID-19 Patients Carry Tenascin-C and Fibrinogen-β in Triggering Inflammatory Signals in Cells of Distant Organ

Abstract: SARS-CoV-2 infection can cause cytokine storm and may overshoot immunity in humans; however, it remains to be determined whether virus-induced soluble mediators from infected cells are carried by exosomes as vehicles to distant organs and cause tissue damage in COVID-19 patients. We took an unbiased proteomic approach for analyses of exosomes isolated from plasma of healthy volunteers and COVID-19 patients. Our results revealed that tenascin-C (TNC) and fibrinogen-β (FGB) are highly abundant in exosomes from C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…A massive increase in secretion of pro-inflammatory molecules, including chemokines such as CCL5 and other cytokines in response to SARS-CoV-2 infection, cause a cytokine storm ( 84 , 321 323 ). Multiple-fold increases in CCL5 expression in severe COVID-19 patients compared to healthy individuals are well documented ( 311 , 312 , 315 , 324 ). Additionally, there was a significant increase in CCL5 expression in non-surviving COVID-19 patients compared to severe, mild and healthy groups ( 313 ).…”
Section: Discussionmentioning
confidence: 99%
“…A massive increase in secretion of pro-inflammatory molecules, including chemokines such as CCL5 and other cytokines in response to SARS-CoV-2 infection, cause a cytokine storm ( 84 , 321 323 ). Multiple-fold increases in CCL5 expression in severe COVID-19 patients compared to healthy individuals are well documented ( 311 , 312 , 315 , 324 ). Additionally, there was a significant increase in CCL5 expression in non-surviving COVID-19 patients compared to severe, mild and healthy groups ( 313 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNC in breast milk binds to the HIV-1 envelope via fibrinogen-like globe (fbg) and fibronectin-type III (fn) domains, which neutralize HIV [ 131 , 132 , 133 ]. In contrast, recent findings indicated that TNC was delivered to the cells of distant organs in COVID-19 patients through plasma exosomes and may trigger pro-inflammatory cytokine signaling as a contributory factor to the cytokine storm [ 134 ]. Furthermore, TNC may modify the disease state of viral infection by interacting with other pathogens.…”
Section: Myocarditismentioning
confidence: 99%
“…EV acting as a "Trojan horse" could explain the re-appearance of the viral RNA in patients recovered from COVID-19 21,52 . EV are involved in SARS-CoV-2 infection [53][54][55] and could be used as biomarkers of disease severity 56 . SARS-CoV-2 RNA has been identi ed in the exosomal cargo of samples from patients with COVID-19, but not in healthy subjects, suggesting that the virus might use the endocytosis route to spread infection 57 .…”
Section: Discussionmentioning
confidence: 99%